Angular responsivity of ground and space-based direct solar irradiance radiometers. Issue 1 (January 2022) - Hülsen, Gregor; Gröbner, Julian; Pfiffner, Daniel; Gyo, Manfred; Kouremeti, Natalia; Föller, Jakob
Abstract: The angular response setup of PMOD/WRC was modified to facilitate measurements of the narrow field of view of radiometers for direct solar irradiance. First, The pointing of the JTSIM-DARA radiometer was measured four times during its construction in the optic laboratory of PMOD/WRC. The final offset of the pointing before shipping relative to the optical axis, defined by a removable alignment cube, is 1.07° / 0.67° ( β / γ -axis) for the four-quadrant sensor and 0.095°/-0.017° for the radiometer cavity A. Next to JTSIM-DARA the DARA for the occulter of the satellite Proba-3 was characterised at PMOD/WRC. First tests of the pointing have been carried out and the final pointing characterization will be carried out in summer 2021. Finally, the angular response setup was also used the angular responsivity of solar direct irradiance filter radiometers. The first test was carried out using Precision Filter Radiometer (PFR) F-064.